Social interest and social bonding: understanding collegiate hazardous drinking and marijuana use - Giordano, Amanda Lee (2012)
The purpose of the current study was to examine both social interest and social bonding in relation to collegiate hazardous drinking and marijuana use. Social interest is a component of Adler's Individual Psychology and refers to one's interest in the welfare of others (Ansbacher, 1992). This construct has been linked to substance abuse in light of Adler's assertions that alcohol and drug abuse are consequences of the failure to develop social interest (Adler, 1956). Social bonding, developed by Travis Hirschi, is a construct stemming from Control Theory. Hirschi posited that one's bond to society is created by four elements, namely, attachment, commitment, involvement, and belief. He asserted that strong social bonding curbs delinquent behavior, which includes all acts punishable by agents of society if discovered, including illegal alcohol and marijuana use (Hirschi, 1969). Therefore, this study examined the relationship between the internal construct of social interest and the external construct of social bonding on college substance abuse in an effort to better understand those students at-risk for hazardous drinking and marijuana use. The sample consisted of 300 full-time undergraduate students who completed a 102 item survey packet. The results of the study supported the notion that social interest and social bonding are related to collegiate hazardous drinking and marijuana use. Specifically, the results of the multiple regression analysis indicated that the social bonding variables of Religious Commitment, Conventional Beliefs, and Respect for Authority accounted for 21% of the variance in collegiate hazardous drinking. Additionally, the results of two omnibus MANOVA tests revealed that both social interest and social bonding variables significantly differed between groups of marijuana users ranging from nonusers to daily users, and significantly differed between substance abuse configurations including those who neither engage in hazardous drinking nor marijuana use, engage in hazardous drinking only, engage in marijuana use only, or engage in both substance abusing behaviors. Finally, the results of a discriminant function analysis indicated that Religious Commitment, Conventional Beliefs, and Respect for Authority were significant predictors of membership in the substance abuse configuration groups. These results have implications for counselors and counselor educators. Counselors working with collegiate populations may benefit by addressing social interest and social bonding elements with their clients through assessments and interventions, as well as incorporating these constructs into their conceptualizations and treatment plans. Counselor educators may best serve counselors-in-training by infusing the constructs of social interest and social bonding into course curriculum. Finally, these results have implications for future research. In the future, researchers should explore each of the significant social interest and social bonding variables that contributed to differences between groups of college students engaged in various configurations of substance abuse